2019
DOI: 10.1186/s12882-019-1466-z
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of clinical characteristics and outcomes of acute kidney injury in a tertiary care Centre

Abstract: Background Acute kidney injury (AKI) is a major global health problem. We aim to evaluate the epidemiology, risk factors and outcomes of AKI episodes in our single centre. Methodology We prospectively identified 422 AKI and acute on chronic kidney disease episodes in 404 patients meeting KDIGO definitions using electronic medical records and clinical data from 15th July to 22nd October 2016, excluding patients with baseline estimated GFR (eGFR) of < 15 mL/min. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 51 publications
2
18
1
1
Order By: Relevance
“…The overall in-hospital mortality of AKI in our study (12.8%) is much lower compared to findings from other studies, 22.6% in Egypt, 36.9% in Cameroon, 44.4% in Malawi and, 20.3% in Singapore 6,16,23,24 . The variation with these studies might be due to; the difference in patient's site of admission (i.e.…”
Section: Discussioncontrasting
confidence: 79%
“…The overall in-hospital mortality of AKI in our study (12.8%) is much lower compared to findings from other studies, 22.6% in Egypt, 36.9% in Cameroon, 44.4% in Malawi and, 20.3% in Singapore 6,16,23,24 . The variation with these studies might be due to; the difference in patient's site of admission (i.e.…”
Section: Discussioncontrasting
confidence: 79%
“…A higher mortality rate among AKI patients in ICU is a major health problem. It is reported that 50% of the death caused by AKI had received suboptimal care and 14% of the death is found avoidable (4). Besides, AKI is frequently associated with ICU admission, intubation and re-intubation, and re-admission of ICU compared to other medical problems (5 -7).…”
Section: Introductionmentioning
confidence: 99%
“…[25] With regards to comorbidities, 302 (74.8%) had hypertension, 230 (56.9%) had diabetes mellitus, and 187 (46.3%) had ischemic heart disease in a study of outcomes of acute kidney injury. [26] Study by Ravindra L Mehta et al, comorbidities associated with AKI are CAD (37%), CKD (37%), DM (29%). [27] Pre-existing CKD increases the risk of non-recovery from AKI.…”
Section: Comorbidities and Acute Kidney Injurymentioning
confidence: 99%